Effect of peripartum micronutrient supplementation on postpartum udder health in high-yielding crossbred cattle - PRADHAN, NEVIDITA; MUKHERJEE, JOYDIP; BISWAS, UJJWAL; JANA, PARTHA SARATHI; GUHA, CHANCHAL (The Indian Journal of Animal Sciences, 2017)
The study was aimed to evaluate the effect of peripartum micronutrient supplementation on postpartum udder health in high-yielding crossbred cows. High-yielding crossbred cows (12) of late pregnancy were selected and divided into two groups, viz. supplemented (6) and unsupplemented (6). Supplemented animals were supplied with a mineral mixture (@25 g daily) fortified with copper (Cu), selenium (Se), manganese (Mn) and zinc (Zn) as per the recommendation of National Research Council (NRC) over and above the normal ration starting from 45 days precalving and continued till 45 days postcalving (based on their expected date of calving). Milk samples from each animal were collected and different attributes of udder immunity were evaluated. The supplemented group exhibited higher udder immunity as depicted by lower milk somatic cell count and higher activity of milk lymphocytes.